Analysis Understanding Financial Risk in Debt Instruments: The Role of Debt Repayment Provisions in Preferred and Common Stock - Deni Sunaryo; Ahmad Firdaus; Fahaina Izzatul Jannah; Ira Firanti Apriliani; Shinta Aprilia Fatimahtuzahra (Management Dynamics: International Journal of Management and Digital Sciences, 2025)
Debt instruments, particularly those related to preferred and common stocks, play an important role in capital markets and corporate finance. One of the crucial elements that influence investment decisions and corporate policies is debt repayment provisions. Preferred stocks, with higher priority in terms of debt repayment, provide a sense of security for investors because they provide greater protection against the risk of loss. In contrast, common stocks, which have lower priority in debt repayment, offer higher potential returns but with greater risks. This article aims to explore the role of debt repayment provisions in common stocks through an in-depth literature review. The methodology used is a thematic and comparative analysis approach to the existing literature, focusing on the differences in debt repayment rights and their impact on investment decisions and corporate policies. The results show that debt repayment provisions have a significant impact on investment stability, where preferred stocks are more beneficial for conservative investors who prioritize security, while common stocks are more suitable for investors seeking potential returns for conservative investors who prioritize security, while common stocks are more suitable for investors seeking potential high returns despite greater risks. This conclusion provides an important contribution to understanding the dynamics of the capital market and helps investors and companies in designing better financial strategies. Further research is needed to explore the direct effect of debt repayment provisions on capital market performance and stock value in companies.